Constructing written scientific explanations: a conceptual analysis supporting diverse and exceptional middle- and high-school students in developing science disciplinary literacy - Moore, Brooke A.; Wright, Jessica (Frontiers in Education, 2023)
Constructing a written scientific explanation is a science practice that is fundamental in supporting students developing understanding of the natural world in which we live. Engaging in the practice of constructing valid scientific explanations supports students in developing science disciplinary literacy. Yet, writing a scientific explanation can be challenging for diverse and exceptional learners because it requires coordinating multiple, complex skills. This conceptual analysis explores the purpose of constructing written scientific explanations by focusing on the constituent elements and structures of a constructed scientific explanation. These findings are then integrated into a framework to assist Individual Education Program (IEP) teams in planning and implementing successful supports and instruction for diverse and exceptional learners in middle-and high-school, general education, science classrooms.